Preparation method of novel nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode material
By treating graphene with hydrogen peroxide and urea, a self-assembled carbon nanotube material of nitrogen-doped porous graphene was prepared, which solved the problem of graphene agglomeration hindering electrolyte contact, and achieved efficient cycling and rate performance of potassium ion batteries , significantly improves the charge transfer efficiency and diffusion rate.
Patent Information
- Application Number
- CN202411032813.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-13
AI Technical Summary
Graphene is prone to agglomeration during charging and discharging, hindering the contact of electrolyte, resulting in poor actual specific capacity, magnification and cycling performance in potassium ion batteries, and unstable structure, affecting long cycle life.
Using hydrogen peroxide as a strong oxidant and urea as a nitrogen dopant, nitrogen-doped porous graphene self-assembled carbon nanotubes are prepared as the negative electrode material of potassium ion battery to form a three-dimensional interconnected porous structure. Adjust the nanopore structure to improve potassium ion transport channel efficiency.
The excellent cycle performance and rate performance of nitrogen-doped porous graphene self-assembled carbon nanotube materials can be achieved, and the capacity can be retained after 500 cycles at 1Ag-1 current density is maintained, which significantly improves the charge transfer efficiency of potassium ion batteries. and diffusion rate.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a novel nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode material, belonging to the technical field of potassium ion battery preparation. Background Art
[0002] Potassium-ion batteries are emerging electrochemical energy storage devices that are expected to be used in electric vehicles and large-scale stationary green energy storage. In order to achieve higher actual specific capacity in potassium-ion batteries, the use of graphite-based negative electrode materials is particularly important. Graphene has attracted widespread attention as a highly promising negative electrode material for rechargeable batteries because of its high intrinsic conductivity, excellent mechanical flexibility and large theoretical surface area (2630m 2 g -1 ). However, due to K + Large size This results in large volume expansion and slow transport kinetics during charge and discharge. In addition, due to the strong π-π interaction between graphene sheets, graphene tends to restack to form graphite-like powder or film, which seriously reduces the specific surface area and ion diffusion rate, resulting in extremely poor reversible specific capacity, rate and cycle performance in practical applications. Therefore, stabilizing the structure of graphene during charge and discharge is particularly important for achieving long cycle life.
[0003] Current research shows that macropores are related to electrolyte penetration, mesopores can provide short diffusion distances, active intercalation sites or rapid ion adsorption, and micropores can provide large specific surface area. In addition, designing low-dimensional materials into porous three-dimensional architectures may help buffer volume changes and shorten diffusion paths. Therefore, in combination with the above-mentioned problems, the present patent proposes a method of using strong oxidants to form pores and heteroatom doping to prepare a series of nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode materials by hydrogen peroxide etching and hydrothermal method. The negative electrode material has good structural stability, cycle performance and rate performance, providing new ideas for the design of advanced carbon negative electrode materials. Summary of the invention
[0004] The purpose of the present invention is to solve the problems that graphene is easy to agglomerate and hinder its contact with the electrolyte, and to improve its performance and promote the development of advanced carbon negative electrode materials. A new process for preparing nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode material is proposed, which uses single-layer graphene oxide as a precursor, hydrogen peroxide as a strong oxidant, urea as a nitrogen dopant, and short multi-walled carbon nanotubes as a composite material.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] The present invention is a method for preparing a nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode material, comprising the following steps:
[0007] S1. Put a single layer of graphene oxide (GO) and deionized water in a beaker for cell crushing, then transfer the dispersion into a glass bottle and add a hydrogen peroxide solution, heat and etch the glass bottle in an oil bath, take out the reagent bottle after etching, cool naturally and perform high-speed centrifugation, wash with hydrochloric acid and deionized water, and freeze-dry the precipitate to obtain reduced graphene oxide (HGO) powder;
[0008] S2, placing the HGO powder obtained in step S1, urea, short multi-walled carbon nanotubes and deionized water in a beaker for cell crushing to obtain a stable dispersion;
[0009] S3, placing the dispersion obtained in step S2 in a reactor for hydrothermal reaction, and freeze-drying the hydrogel obtained by hydrothermal reaction to obtain nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material.
[0010] Specifically, in step S1, the addition amount of monolayer graphene oxide is 100-500 mg, the deionized water is 120-180 ml, the cell crushing time is 10-30 min, the ultrasonic power is 40-80%, the hydrogen peroxide concentration is 10-70%, the oil bath temperature is 90-100° C., the heating etching time is 1-6 h, the hydrochloric acid concentration is 0.1-0.5 M, the freezing time is 12-24 h, and the drying time is 12-48 h;
[0011] Specifically, in step S2, the mass ratio of urea to HGO is 10:1-70:1, the mass ratio of short multi-walled carbon nanotubes to HGO is 5-20wt.%, the amount of deionized water is 30-70ml, the cell pulverization time is 10-30min, and the ultrasonic power is 40-80%;
[0012] Specifically, in step S3, the hydrothermal reaction temperature is 150-180° C., the hydrothermal time is 4-8 hours, the freezing time is 12-24 hours, and the drying time is 12-48 hours.
[0013] The further claimed potassium ion battery preparation process comprises the following steps:
[0014] (1) The prepared nitrogen-doped porous graphene self-assembled carbon nanotube material, conductive carbon black and binder (PVDF) were mixed in a mass ratio of 8:1:1 and an appropriate amount of N-methylpyrrolidone (NMP) was added to form a slurry, which was then coated on a copper foil current collector. The electrode sheet was dried in a vacuum drying oven at 110°C for 12 h, and after drying, it was cut into 12 mm electrode sheets for standby use.
[0015] (2) CR2032 button cells were used to assemble the battery. The entire battery assembly process was completed in a glove box with a water and oxygen content of less than 0.01 ppm. Metal potassium was used as the counter electrode, the diaphragm was Whatman GF / D glass fiber, the electrolyte was 0.8M KPF6in DEC / EC, and the working electrode was the above-mentioned 12 mm electrode disc. The assembly order was negative electrode shell, metal potassium foil, diaphragm (fully wetted with electrolyte), electrode disc, gasket, shrapnel and positive electrode shell. The button cell was tested after standing for 8 hours.
[0016] Compared with the prior art, the present invention provides a novel method for preparing a negative electrode material of a potassium ion battery of nitrogen-doped porous graphene self-assembled carbon nanotubes, which has the following benefits:
[0017] 1. The method adopted by the present invention can prepare materials with three-dimensional interconnected porous morphology, rich doping defects and nanopore distribution. The process is relatively simple and can achieve large-scale production.
[0018] 2. The present invention provides a nitrogen-doped porous graphene self-assembled carbon nanotube material, which has excellent cycle performance and rate performance when used as anode material of potassium ion battery; -1 After 500 cycles at a current density of , 85.3% of the capacity can be retained, which can meet application requirements.
[0019] 3. Hydrogen peroxide oxidative etching can adjust the nanopore structure. The abundant nanopores construct efficient potassium ion transmission channels. The pore structure and nitrogen doping effectively reduce the charge transfer impedance of graphene negative electrode materials and increase the potassium ion diffusion coefficient. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described below with specific embodiments, but is not limited to the following implementation cases.
[0021] Example 1
[0022] (1) 300 mg of single-layer graphene oxide (GO) and 150 ml of deionized water were placed in a beaker for cell crushing, the ultrasonic power was 60%, and the ultrasonic time was 15 min. Then the dispersion was transferred to a 250 ml glass bottle and a 30% hydrogen peroxide aqueous solution was added. The glass bottle was subjected to oil bath heating etching, the oil bath temperature was 95 ° C, and the heating etching time was 4 h. After the etching time was reached, the reagent bottle was taken out, and after natural cooling, it was centrifuged at a speed of 10000 rpm for 20 min. After washing with 0.1 M hydrochloric acid and deionized water, the precipitate was frozen for 12 h and dried for 48 h to obtain reduced graphene oxide HGO-4h powder;
[0023] (2) adding 6 g of urea to the HGO-4h powder obtained in step (1) at a mass ratio of 1:50 to urea, adding short multi-walled carbon nanotubes to the HGO-4h powder obtained in step (1) at a mass ratio of 1:10 wt.%, and then adding 60 ml of deionized water to crush the cells, and the ultrasonic power is 60%, and the ultrasonic time is 15 min to form a dispersion;
[0024] (3) placing the dispersion obtained in step (2) in a reactor and subjecting it to hydrothermal reduction at 180°C for 6 hours to obtain nitrogen-doped porous graphene self-assembled carbon nanotube hydrogel, then freezing the hydrogel for 12 hours and drying it for 48 hours to obtain nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material.
[0025] The potassium ion battery assembled with the nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material prepared in Example 1 was -1 The initial discharge capacity at the current density is 265 mAh g -1 After 150 cycles, the capacity is 153 mAh g -1 Compared with the third cycle, the capacity retention rate was 73.0% at 1A g -1 The capacity retention rate is 85.3% after 500 cycles at the current density.
[0026] Example 2
[0027] (1) 300 mg of single-layer graphene oxide (GO) and 150 ml of deionized water were placed in a beaker for cell crushing, the ultrasonic power was 60%, and the ultrasonic time was 15 min. Then the dispersion was transferred to a 250 ml glass bottle and a 30% hydrogen peroxide aqueous solution was added. The glass bottle was subjected to oil bath heating etching, the oil bath temperature was 95 ° C, and the heating etching time was 6 h. After the etching time was reached, the reagent bottle was taken out, and after natural cooling, it was centrifuged at a speed of 10000 rpm for 20 min. After washing with 0.2 M hydrochloric acid and deionized water, the precipitate was frozen for 12 h and dried for 48 h to obtain reduced graphene oxide HGO-6h powder;
[0028] (2) adding 3.6 g of urea to the HGO-6h powder obtained in step (1) at a mass ratio of 1:30 to urea, adding short multi-walled carbon nanotubes to the HGO-6h powder obtained in step (1) at a mass ratio of 1:10 wt.%, and then adding 60 ml of deionized water to crush the cells, and the ultrasonic power is 60%, and the ultrasonic time is 15 min to form a dispersion;
[0029] (3) placing the dispersion obtained in step (2) in a reactor and subjecting it to hydrothermal reduction at 180°C for 6 hours to obtain nitrogen-doped porous graphene self-assembled carbon nanotube hydrogel, then freezing the hydrogel for 12 hours and drying it for 48 hours to obtain nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material.
[0030] The potassium ion battery assembled with the nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material prepared in Example 2 was -1 The initial discharge capacity at the current density is 246 mAh g -1 After 150 cycles, the capacity is 117 mAh g -1 Compared with the third cycle, the capacity retention rate was 70.1% at 1A g -1 The capacity retention rate is 82.3% after 500 cycles at the current density.
[0031] Example 3
[0032] (1) 300 mg of single-layer graphene oxide (GO) and 150 ml of deionized water were placed in a beaker for cell crushing, the ultrasonic power was 60%, and the ultrasonic time was 15 min. Then the dispersion was transferred to a 250 ml glass bottle and a 50% hydrogen peroxide aqueous solution was added. The glass bottle was subjected to oil bath heating etching, the oil bath temperature was 90 ° C, and the heating etching time was 6 h. After the etching time was reached, the reagent bottle was taken out, and after natural cooling, it was centrifuged at a speed of 10000 rpm for 20 min. After washing with 0.1 M hydrochloric acid and deionized water, the precipitate was frozen for 12 h and dried for 48 h to obtain reduced graphene oxide HGO-6h powder;
[0033] (2) adding 3.6 g of urea to the HGO-6h powder obtained in step (1) at a mass ratio of 1:30 to urea, adding short multi-walled carbon nanotubes to the HGO-6h powder obtained in step (1) at a mass ratio of 1:20 wt.%, and then adding 60 ml of deionized water to crush the cells, and the ultrasonic power is 60%, and the ultrasonic time is 15 min to form a dispersion;
[0034] (3) The dispersion obtained in step (2) is placed in a reactor and subjected to hydrothermal reduction at 160° C. for 6 h to obtain nitrogen-doped porous graphene self-assembled carbon nanotube hydrogel, and then the hydrogel is frozen for 12 h and dried for 48 h to obtain nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material.
[0035] The potassium ion battery assembled with the nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material prepared in Example 3 has a conductivity of 0.05A g -1 The initial discharge capacity at the current density is 245 mAh g -1 After 150 cycles, the capacity is 78 mAh g-1 Compared with the third cycle, the capacity retention rate was 56.4% at 1A g -1 The capacity retention rate was 76.6% after 500 cycles at the current density.
[0036] Example 4
[0037] ((1) 300 mg of single-layer graphene oxide (GO) and 150 ml of deionized water were placed in a beaker for cell crushing, the ultrasonic power was 60%, and the ultrasonic time was 15 min. The dispersion was then transferred to a 250 ml glass bottle and a 30% hydrogen peroxide aqueous solution was added. The glass bottle was subjected to oil bath heating etching at an oil bath temperature of 90°C for a heating etching time of 2 h. After the etching time was reached, the reagent bottle was taken out, and after natural cooling, the mixture was centrifuged at a speed of 10,000 rpm for 20 min. After washing with 0.1 M hydrochloric acid and deionized water, the precipitate was frozen for 12 h and dried for 48 h to obtain reduced graphene oxide HGO-2h powder;
[0038] (2) adding 6 g of urea to the HGO-2h powder obtained in step (1) at a mass ratio of 1:50 to urea, adding short multi-walled carbon nanotubes to the HGO-2h powder obtained in step (1) at a mass ratio of 1:20 wt.%, and then adding 60 ml of deionized water to crush the cells, and the ultrasonic power is 60%, and the ultrasonic time is 15 min to form a dispersion;
[0039] (3) The dispersion obtained in step (2) is placed in a reactor and subjected to hydrothermal reduction at 180° C. for 4 h to obtain nitrogen-doped porous graphene self-assembled carbon nanotube hydrogel, and then the hydrogel is frozen for 12 h and dried for 48 h to obtain nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material.
[0040] The potassium ion battery assembled with the nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material prepared in Example 4 was -1 The initial discharge capacity at the current density is 252 mAh g -1 After 150 cycles, the capacity is 85 mAh g -1 Compared with the third cycle, the capacity retention rate was 58.2% at 1A g -1 The capacity retention rate is 78.2% after 500 cycles at the current density.
[0041] Example 5
[0042] (1) 300 mg of single-layer graphene oxide (GO) and 150 ml of deionized water were placed in a beaker for cell crushing, the ultrasonic power was 60%, and the ultrasonic time was 15 min. Then the dispersion was transferred to a 250 ml glass bottle and a 50% hydrogen peroxide aqueous solution was added. The glass bottle was subjected to oil bath heating etching, the oil bath temperature was 90 ° C, and the heating etching time was 4 h. After the etching time was reached, the reagent bottle was taken out, and after natural cooling, it was centrifuged at a speed of 10000 rpm for 20 min. After washing with 0.1 M hydrochloric acid and deionized water, the precipitate was frozen for 12 h and dried for 48 h to obtain reduced graphene oxide HGO-4h powder;
[0043] (2) adding 3.6 g of urea to the HGO-4h powder obtained in step (1) at a mass ratio of 1:30 to urea, adding short multi-walled carbon nanotubes to the HGO-4h powder obtained in step (1) at a mass ratio of 1:5 wt.%, and then adding 60 ml of deionized water to crush the cells, and the ultrasonic power is 60%, and the ultrasonic time is 15 min to form a dispersion;
[0044] (3) placing the dispersion obtained in step (2) in a reactor and subjecting it to hydrothermal reduction at 180°C for 6 hours to obtain nitrogen-doped porous graphene self-assembled carbon nanotube hydrogel, then freezing the hydrogel for 12 hours and drying it for 48 hours to obtain nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material.
[0045] The potassium ion battery assembled with the nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material prepared in Example 5 was -1 The initial discharge capacity at the current density is 364 mAh g -1 After 150 cycles, the capacity is 208 mAh g -1 Compared with the third cycle, the capacity retention rate was 45.6% at 1A g -1 The capacity retention rate is 70.3% after 500 cycles at the current density.
[0046] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A method for preparing a nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode material, characterized in that: The preparation method of the negative electrode material of the potassium ion battery comprises the following steps: S1. Put a single layer of graphene oxide (GO) and deionized water in a beaker for cell crushing, then transfer the dispersion into a glass bottle and add a hydrogen peroxide solution, heat and etch the glass bottle in an oil bath, take out the reagent bottle after etching, cool naturally and perform high-speed centrifugation, wash with hydrochloric acid and deionized water, and freeze-dry the precipitate to obtain reduced graphene oxide (HGO) powder; S2, placing the HGO powder obtained in step S1, urea, short multi-walled carbon nanotubes and deionized water in a beaker for cell crushing to obtain a stable dispersion; S3, placing the dispersion obtained in step S2 in a reactor for hydrothermal reaction, and freeze-drying the hydrogel obtained by hydrothermal reaction to obtain nitrogen-doped porous graphene self-assembled carbon nanotube negative electrode material.
2. The method for preparing a nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode material according to claim 1, characterized in that: The addition amount of single-layer graphene oxide is 100-500 mg, the deionized water is 120-180 ml, the cell crushing time is 10-30 min, the ultrasonic power is 40-80%, the hydrogen peroxide concentration is 10-70%, the oil bath temperature is 90-100° C., the heating etching time is 1-6 h, the hydrochloric acid concentration is 0.1-0.5 M, the freezing time is 12-24 h, and the drying time is 12-48 h.
3. The method for preparing a nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode material according to claim 1, characterized in that: In step S2, the mass ratio of urea to HGO is 10:1-70:1, the mass ratio of short multi-walled carbon nanotubes to HGO is 5-20wt.%, the amount of deionized water is 30-70ml, the cell pulverization time is 10-30min, and the ultrasonic power is 40-80%.
4. The method for preparing a nitrogen-doped porous graphene self-assembled carbon nanotube potassium ion battery negative electrode material according to claim 1, characterized in that: In step S3, the hydrothermal reaction temperature is 150-180° C., the hydrothermal time is 4-8 hours, the freezing time is 12-24 hours, and the drying time is 12-48 hours.
Citation Information
Patent Citations
Fluorine-nitrogen dual-doped porous graphene hydrogel for supercapacitor electrode and preparation method thereof
CN109678139A
Nitrogen-doped graphene anode material, preparation method thereof, and lithium ion battery
CN110247032A
Nitrogen-doped three-dimensional porous graphene-based electrode material as well as preparation method and application thereof
CN111943179A
Method for preparing nitrogen-doped porous reduced graphene oxide from recycled negative electrode graphite materials of waste lithium ion batteries
CN113651320A
